Detecting plasmid-mediated dissemination of blaKPC-3 and blaOXA-48-like genes in Enterobacterales across Finnish healthcare organizations using hybrid genome assembly - Piispa, Meeri; Vainio, Anni; Halkilahti, Jani; Lyytikäinen, Outi; Räisänen, Kati (Frontiers in Microbiology, 2025)
The spread of carbapenemase-producing Enterobacterales (CPE) is a global concern. While the majority of the CPE outbreaks are due to clonal spread, recent findings highlight the transmission of carbapenemase gene-carrying plasmids across various bacterial species, exacerbated by extensive antibiotic use in hospitals. This study aimed to identify plasmid-mediated horizontal transfer of carbapenemase genes among Enterobacterales isolated from patient samples and hospital environment samples in three healthcare organizations in Finland. Using a hybrid assembly of short and long reads, we could complete the genome assembly and compare the plasmids harboring the blaKPC-3 and blaOXA-48-like genes. Our findings reveal indications of interspecies and intraspecies plasmid-mediated gene transfer of blaKPC-3 and blaOXA-48-like, emphasizing the role of horizontal gene transfer (HGT) in outbreaks. The study underscores the need for comprehensive infection control and surveillance beyond specific species to prevent the spread of antimicrobial resistance genes. These results suggest that expanding outbreak investigations to an interspecies level could be beneficial.